Prevalence of SARS-CoV-2 antibodies after the Omicron surge, Kingston, Jamaica, 2022 - Joshua J. Anzinger; Suzette M. Cameron-McDermott; Yakima Z.R. Phillips; Leshawn Mendoza; Mark Anderson; Gavin Cloherty; Susan Strachan-Johnson; John F. Lindo; J. Peter Figueroa (Journal of Clinical Virology Plus, 2022)
ABSTRACT: A cross-sectional SARS-CoV-2 serosurvey was conducted after the Omicron surge in Jamaica using 1,540 samples collected during March – May 2022 from persons attending antenatal, STI and non-communicable diseases clinics in Kingston, Jamaica. SARS-CoV-2 spike receptor binding domain (RBD) and/or nucleocapsid IgG antibodies were detected for 88.4% of the study population, with 77.0% showing evidence of previous SARS-CoV-2 infection. Of persons previously infected with SARS-CoV-2 and/or with COVID-19 vaccination, 9.6% were negative for spike RBD IgG, most of which were unvaccinated previously infected persons. Amongst unvaccinated previously infected people, age was associated with testing spike RBD IgG negative. When considering all samples, median spike RBD IgG levels were 131.6 BAU/mL for unvaccinated persons with serological evidence of past infection, 90.3 BAU/mL for vaccinated persons without serological evidence of past infection, and 896.1 BAU/mL for vaccinated persons with serological evidence of past infection. Our study of the first reported SARS-CoV-2 serosurvey in Jamaica shows extensive SARS-CoV-2 population immunity, identifies a substantial portion of the population lacking spike RBD IgG, and provides additional evidence for increasing COVID-19 vaccine coverage in Jamaica.